Evaluation of the Sustainable Food Garden Program (P2L) During the Covid-19 Pandemic in Garut Regency - Yuma Iza; Evi Satispi; Rahmat Salam; Retnowati WD Tuti (Program Pascasarjana Universitas Negeri Makassar, 2021)
The purpose of this study was to analyze the evaluation of the Sustainable Food Garden (P2L) program during the Covid-19 pandemic in Garut Regency, implemented by the Food Security Agency (DKP) using the CIPP Evaluation Model. The Food Security Agency (BKP), the Ministry of Agriculture through the Food Security Service from 2010 to 2019 has implemented Sustainable Food House Area Activities (KRPL) through optimizing the use of yard land. Since 2020, it has been transformed into a Sustainable Food Garden (P2L). This study uses a qualitative method. The research is descriptive (descriptive research), that is, describes the actual situation in accordance with the object of research. Data collection techniques were carried out using observation techniques in five farmer groups/women farmer groups in Garut Regency and in-depth interviews with ten informants who were directly involved with the Sustainable Food Garden (P2L) program. The results showed that the Sustainable Food Garden Program (P2L) in Garut Regency had been running well and effectively starting from the submission, distribution of the assistance to farmer groups/KWT as well as assistance carried out by the local office and extension workers in the fields. Although in implementation there are still some obstacles faced in the field. During the COVID-19 pandemic, the P2L program was an alternative solution to fulfill family food security. The impact is felt by the farmer groups/KWT and the surrounding community. Through the P2L program.